Minor actinides burning in a stellarator-mirror fusion-fission hybrid - Chernitskiy, S.V.; Moiseenko, V.E.; Ågren, O.; Noack, K. (Вопросы атомной науки и техники, 2015)
The MCNPX Monte-Carlo code has been used to model a compact concept of a fusion-fission reactor based on a combined stellarator-mirror trap for transmutation transuranic elements from the spent nuclear fuel. Calculation results for fission rates for transuranic elements are presented.